ENCULTURATION AND GENDER IN WOVEN FABRICT INDUSTRY AT SUBDISTRICT OF SANGKARAGUNG, DISTRICT OF NEGARA, JEMBRANA - Sukardja, Putu; Parimartha, I Gde; Ardika, I Wayan; Suastika, I Made (E-Journal of Cultural Studies, 2009)
This research reveals the process of enculturation and gender in the woven fabricindustry at Sangkaragung, district of Negara, Jembrana. The weaving tradition andenculturation process give the women at Sangkaragung a hope to change their ideology ingender and socio cultural construction. This study aims at discussing the factors makingthe women at Sangkaragung do weaving activities, the process of weaving enculturationand the development of gender taking place there, and the impacts and meaning of theweaving enculturation on their socio-cultural life.In analyzing the problems above, the theory of post-structuralism, the theory ofpractice, and the theory of social change were used. To find out the relevant data, aqualitative method was applied in which the data were collected by deep interviews,observation, and documentation.The result shows that the factors making the women do such activities are: mythson women and weaving activities; globalization and socio-cultural changes, and fulfillmentof daily needs. The process of weaving enculturation done through cultural transmissionand socialization in weaving results in acculturation and enculturation which then give adeeper understanding to the society of the pattern and system related to the weavingactivities. The weaving enculturation also causes some forms of changes at Sangkaragungsuch as work division between men and women. The weaving enculturation and thedevelopment of gender have affected the ways in which decisions are made in someaspects of life such as in the context of traditional and religious rituals, the expenditures forprimary family needs, health care, and children’s education. Although the women areacknowledged and appreciated that they have economically contributed to their families,full emancipation has not been given to them due to patriarchal, social and cultural systemswhich are still attached to the society.